AN ENHANCE CORRUPTION ERADICATION THROUGH A POLITICAL LEGAL APPROACH - Ismaidar Ismaidar; Sukardi Sukardi (Jurnal Scientia, 2023)
The word corruption comes from Latin, namely corruptio or corruptus, which means "rottenness, ugliness, crime, dishonesty, corruptibility, immorality, deviation from purity". Corruption in Indonesia is a recurrent and emergency national problem that Indonesia has faced from time to time over a relatively long period of time, so it is hoped that special corruption courts can help resolve a number of past corruption crimes in order to restore lost assets. Eradicating corruption is a complex and complicated problem that is difficult to overcome quickly, this is proven by the many laws and regulations in each country, but there are still many acts of corruption. This research discusses more about eradicating corruption through a political-legal approach. The problem formulation in this research is how to eradicate corruption through a political-legal approach. The aim of this research is to find out and analyze the eradication of corruption through a political-legal approach. The data collection method in this research is by conducting a literature study of laws and regulations, articles, books and research results, as well as expert opinions related to eradicating corruption through a political-legal approach. The birth of various laws regulating the eradication of criminal acts of corruption was influenced by the political conditions when each law was born. Eradicating corruption in Indonesia through a political-legal approach, namely by enacting laws, especially Law no. 31 Yr. 1999 in conjunction with Law no. 20 of 2001 concerning the Eradication of Corruption Crimes, established the KPK through Law no. 30 of 2002 and established the Financial Transaction Reports and Analysis Center (PPATK) through Law no. 08 Th 2010, creating Law no. 11 of 1980 concerning the Crime of Bribery, although this is not enough to eradicate criminal acts of corruption in Indonesia.